Changes in extra-striatal functional connectivity in patients with schizophrenia in a psychotic episode. (January 2017) - Peters, Henning; Riedl, Valentin; Manoliu, Andrei; Scherr, Martin; Schwerthöffer, Dirk; Zimmer, Claus; Förstl, Hans; Bäuml, Josef; Sorg, Christian; Koch, Kathrin
Abstract : Background: In patients with schizophrenia in a psychotic episode, intra-striatal intrinsic connectivity is increased in the putamen but not ventral striatum. Furthermore, multimodal changes have been observed in the anterior insula that interact extensively with the putamen. Aims: We hypothesised that during psychosis, putamen extra-striatal functional connectivity is altered with both the anterior insula and areas normally connected with the ventral striatum (i.e. altered functional connectivity distinctiveness of putamen and ventral striatum). Method: We acquired resting-state functional magnetic resonance images from 21 patients with schizophrenia in a psychotic episode and 42 controls. Results: Patients had decreased functional connectivity: the putamen with right anterior insula and dorsal prefrontal cortex, the ventral striatum with left anterior insula. Decreased functional connectivity between putamen and right anterior insula was specifically associated with patients' hallucinations. Functional connectivity distinctiveness was impaired only for the putamen. Conclusions: Results indicate aberrant extra-striatal connectivity during psychosis and a relationship between reduced putamen–right anterior insula connectivity and hallucinations. Data suggest that altered intrinsic connectivity links striatal and insular pathophysiology in psychosis.